The Existence Of Sodiq New Monata In The Indonesian National Dangdut Music Scene - Galuh Wenda Mayangsari; Tomy Agung Sugito (Universitas Negeri Surabaya, 2024)
This study aims to describe the existence of Sodiq New Monata in the Indonesian national dangdut music scene through the perspective of Soren Kierkegaard's theory of existence and to identify the factors influencing the sustainability of his existence. This research employed a descriptive qualitative approach. Data were collected through observations, in-depth interviews, and documentation. Data trustworthiness was established using source, technique, and time triangulation, while data were analyzed using the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing. The findings reveal that Sodiq New Monata's existence is reflected in Kierkegaard's three stages of existence. The aesthetic stage is characterized by the pursuit of pleasure during his youth, which later transformed into a consciously managed personal branding strategy. The ethical stage is manifested through his leadership responsibility toward New Monata, while the religious stage is reflected in gratitude as the highest expression of worship. Furthermore, his continued existence is supported by internal factors, including strong personal branding, adaptability, leadership, and humility, as well as external factors such as family support, close relationships with fans, effective utilization of digital media, extensive networks within the music industry, and collaborative relationships with fellow musicians. This study demonstrates that the sustainability of a dangdut musician's existence is determined not only by artistic competence but also by consistency, responsibility, and the ability to adapt to the changing dynamics of the contemporary music industry.